Mauá e a tradição de modernizaçaõ Industrial no Brasil - Rafael Rodrigo Ruela Souza (2007)
This is a study that, beginning with the analysis of the political representations around the figure of Irineu Evangelista of Souza, the viscount Mauá, initially built in his own autobiographical narrative and, later re-taken in a biographical narrative, considered the first important biography on the viscount, longs to surprise the foundations of a new political rationality which was being stablished during the 1920s and 1930s. The central hypothesis here defended is that the self-portrait elaborated by Mauá in his Exhibition to the creditors, being reappropriated by Alberto de Faria in the 1920s, would have been responsible for the viscount's entrance in the national civic pantheon. Later, another intellectual, Azevedo Amaral, taking advantage of the force of the archetypal image of Mauá and of the contributions of the economical historiography, then emergent in the country, would have, in a series of essays of interpretation of Brazil written throughout the 1930s, given the decisive step for the appearance of a new tradition in the Brazilian social thought: the industrial modernization